Pengaruh Brand Reputation, Brand Competence, dan Brand Liking terhadap Keputusan Pembelian - ., Santoso; ., Sulistiono (LPPM Institut Bisnis dan Informatika Kesatuan, 2017)
Brand reputation, is a brand that refers to a person to assume that such brand is good and reliable. Brand competence is the ability of product to solve problems faced by its customers, and meet their needs. Brand liking is a particular fondness of one party against another party because these parties find that the other party favorable and suitable. Purchase decision is the stage in the buyer's decision making process, where consumers actually buy the product. This study is to determine the effect of brand reputation, brand competence and brand liking, on purchasing decision of the consumers of motorcycle Yamaha V-Ixion. This research uses a survey approach to retrieve data using questionnaires with respondents of 100 consumers of motorcycle yamaha v-Ixion in Bogor. Based on the calculations, the table variable regression equation brand reputation 0.005 states that each additional values ​​in brand reputation will give rise to a score of 0.005. While the table variable regression equation brand competance 0.090 states that each additional values of variables brand competence will give rise to a score of 0.090. And table variable regression equation of brand liking of 0.531 states that each additional values of brand liking will give rise to a score of 0,531. From the analysis of determination test, brand reputation, brand competence and brand liking, on the purchasing decision is of 0.247, this indicates the relationship between the independent variables are brand reputation, brand competence, and the dependent variables purchasing decisions by 24.7%.